Experimental Study of Spatial Self-Phase Modulation (SSPM) Based on Laser Beam and Hybrid Functionalized Carbon Nanotubes/Silver Nanoparticles (F-Mwcnts/Ag-Nps) Acetone Suspensions - Aboob, Eman A.; Umran, Fadhil A. (Iraqi Journal of Laser, 2019)
Focusing of Gaussian laser beam through nonlinear media can induce spatial self- phase modulation which forms a far field intensity pattern of concentric rings. The nonlinear refractive index change of material depends on the number of pattern rings. In this paper, a formation of tunable nonlinear refractive index change of hybrid functionalized carbon nanotubes/silver nanoparticles acetone suspensions (F-MWCNTs/Ag-NPs) at weight mixing ratio of 1:3 and volume fraction of 6x10-6 , 9x10-6 , and 18x10-6 using laser beam at wavelength of 473nm was investigated experimentally. The results showed that tunable nonlinear refractive indices were obtained and increasing of incident laser power density led to increase the nonlinear refractive index changes of suspension at each volume fraction. Moreover, the nonlinear refractive index changes ( Δnnl,max ) at volume fraction of 18x 10-6 irradiated by various laser intensities (137.31, 200, 228, 268, and 366.61 W/cm2) have higher value than others.